2016
DOI: 10.1002/anie.201601135
|View full text |Cite
|
Sign up to set email alerts
|

Open‐Pore Two‐Dimensional MFI Zeolite Nanosheets for the Fabrication of Hydrocarbon‐Isomer‐Selective Membranes on Porous Polymer Supports

Abstract: Two-dimensional zeolite nanosheets that do not contain any organic structure-directing agents were prepared from a multilamellar MFI (ML-MFI) zeolite. ML-MFI was first exfoliated by melt compounding and then detemplated by treatment with a mixture of H2 SO4 and H2 O2 (piranha solution). The obtained OSDA-free MFI nanosheets disperse well in water and can be used for coating applications. Deposits made on porous polybenzimidazole (PBI) supports by simple filtration of these suspensions exhibit an n-butane/isobu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
56
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 104 publications
(57 citation statements)
references
References 29 publications
1
56
0
Order By: Relevance
“…The first report on a nanosheet‐based highly‐selective separation membrane used secondary growth of nanosheet seed layers, which were prepared by exfoliation of layered MFI using melt‐blending, and deposited using filtration. Following this demonstration, improvements in exfoliation and gel‐free secondary growth led to better separation performances, while the discovery of non‐thermal de‐templation by piranha treatment allowed selective membrane formation on porous polymer supports . Similar approaches have been developed in parallel for graphene oxide and MOF‐based membranes with promising separation performances.…”
Section: Figurementioning
confidence: 96%
“…The first report on a nanosheet‐based highly‐selective separation membrane used secondary growth of nanosheet seed layers, which were prepared by exfoliation of layered MFI using melt‐blending, and deposited using filtration. Following this demonstration, improvements in exfoliation and gel‐free secondary growth led to better separation performances, while the discovery of non‐thermal de‐templation by piranha treatment allowed selective membrane formation on porous polymer supports . Similar approaches have been developed in parallel for graphene oxide and MOF‐based membranes with promising separation performances.…”
Section: Figurementioning
confidence: 96%
“…[2] Microporous membranes,r epresented by zeolite membranes,c an realize excellent separation performances owing to their sieving characteristic based on the pores.Nevertheless,the thickness of these inorganic microporous membranes is generally on the micrometer scale to reduce non-selective defects,w ith lower flux as ap enalty.R ecently,agreat deal of twodimensional (2D) materials have been considered as asuperb building platform for the next generation of separation membranes due to the ideal molecular-unit thickness and the extreme low mass-transfer barrier, [3,4] such as graphene oxide, [5] layered transition-metal dichalcogenides, [6] layered double hydroxides, [7] and 2D zeolite nanosheets. [8] These nanosheets can be assembled layer-by-layer to form selective membranes.G as molecules would pass through the mem-branes via the micropores of the nanosheets or the welldefined interlayer space,hence achieving high gas separation efficiency.…”
mentioning
confidence: 99%
“…[16,17] Thef irst report on an anosheet-based highly-selective separation membrane [18] used secondary growth of nanosheet seed layers,w hich were prepared by exfoliation of layered MFI [19] using melt-blending, [20] and deposited using filtration. [24] Similar approaches have been developed in parallel for graphene oxide [25] and MOF-based membranes [26,27] with promising separation performances.R ecently,i tw as demonstrated that zeolite nanosheets can be prepared by direct (bottom-up) synthesis,t hat is,without the need of exfoliation. [24] Similar approaches have been developed in parallel for graphene oxide [25] and MOF-based membranes [26,27] with promising separation performances.R ecently,i tw as demonstrated that zeolite nanosheets can be prepared by direct (bottom-up) synthesis,t hat is,without the need of exfoliation.…”
mentioning
confidence: 99%